2018
DOI: 10.1002/gps.5003
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive brain stimulation for behavioural and psychological symptoms of dementia: A systematic review and meta‐analysis

Abstract: Background Pharmacological and conventional nonpharmacological treatments for behavioural and psychological symptoms of dementia (BPSD) have only modest efficacy. Furthermore, pharmacotherapy carries the risk of important side effects. Noninvasive brain stimulation (repetitive transcranial magnetic stimulation (TMS) or transcranial direct current stimulation (tDCS)) are valuable and safe for cognitive function in Alzheimer disease (AD). However, there have been few studies, and there is no consensus, regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 35 publications
(131 reference statements)
1
23
0
1
Order By: Relevance
“…Robust synaptic plasticity is critical for cognitive processes, such as learning and memory [7]. Liao and Sara et al demonstrated the efficacy of rTMS on cognitive function and behavioral psychiatric symptoms of AD [2,8]. In addition, the correlation analysis in our study demonstrated improvement in cognition assessment in addition to the improvement in depression symptoms (p > 0.05; see supplemental material).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Robust synaptic plasticity is critical for cognitive processes, such as learning and memory [7]. Liao and Sara et al demonstrated the efficacy of rTMS on cognitive function and behavioral psychiatric symptoms of AD [2,8]. In addition, the correlation analysis in our study demonstrated improvement in cognition assessment in addition to the improvement in depression symptoms (p > 0.05; see supplemental material).…”
supporting
confidence: 63%
“…Presently, successful neuroprotective or curative treatments for AD are lacking [1]. However, one promising alternative therapy is repetitive Transcranial Magnetic Stimulation (rTMS) [2]. Most studies have chosen the dorsolateral prefrontal cortex (DLPFC) as the stimulus target because of its neuroplasticity and important role in cognitive functions (such as association memory) [3].…”
mentioning
confidence: 99%
“…(11) Limit the vicious circle of autodestructive events due to the increased Ca2+ influx resulting from excessive membrane depolarization or intra-axonal Na+ overload in the context of ischemia or energetic resource failure. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]…”
Section: How Tdcs Work On Cognitive Functionmentioning
confidence: 99%
“…Although the application of these methods has reportedly contributed to the positive outcomes in clinical states (e.g., see Lefaucheur et al, 2020 ), the effects induced in the brain are not fully understood. According to the growing number of meta-analyses, the efficacy of brain stimulation methods is inconsistent across different conditions, e.g., depression (Razza et al, 2020 ; Sonmez et al, 2019 ; Moffa et al, 2020 ), mild cognitive impairments and dementia (Vacas et al, 2019 ; Chou et al, 2020 ; Wang et al, 2020 ), anxiety and post-traumatic stress (Cirillo et al, 2019 ), autism spectrum disorders (Barahona-Corrêa et al, 2018 ), ADHD (Salehinejad et al, 2019 ), positive and negative symptoms of schizophrenia (Aleman et al, 2018 ; Kim et al, 2019 ; Yang et al, 2019 ). Further research could benefit from the combination of NIBS with different neurophysiological measures like ASSR.…”
Section: Introductionmentioning
confidence: 99%